Iconographic and archaeometric studies on the rock art at Musayqira, Al‐Quwaiyah Governorate, central Saudi Arabia. (26th April 2021) - Andreae, Meinrat O.; Al‐Amri, Abdullah; Al‐Jibrin, Faisal Hamad; Alsharekh, Abdullah M.
Abstract: We investigated the rock art (petroglyphs) in the Al‐Quwaiyah Governorate (Saudi Arabia) with focus on the Musayqira site. Iconographic analysis showed a broad variety of human depictions, game animals (ibex, ass, ostrich, lion, etc.), domestic animals (cattle, camel, horse, dog, etc.), inscriptions and abstract symbols. Archaeometric measurements by pXRF provided the areal densities of Mn on petroglyphs and intact rock varnish. Varnish accumulation rates were derived from Mn density measurements on inscriptions of known approximate age. Applying these rates to varnish densities on the petroglyphs yielded age estimates. Some of the rock art was incised in fracture fill rather than true varnish, complicating the interpretation of the data. The combination of iconographic and archaeometric data indicated multiple phases of rock art creation, corresponding to the Late Neolithic, Bronze Age, Iron Age, and Islamic Period, with different artistic traditions, reflecting changing socioeconomic and ecological conditions.